Factors of the formation of landscape diversity of the natural park "Foothills of the Altai" and ways to preserve it - O. N. Baryshnikova; I. N. Rotanova; M. M. Silantyeva; N. F. Kharlamova (Acta Biologica Sibirica, 2017)
The article discusses the importance of the factors of the formation of the landscape structure and landscape diversity for the creation of a natural park for the purpose of nature protection and the development of recreational nature management. The results of landscape studies performed in the process of substantiating the creation of a national park of regional significance "Foothills of Altai" in the vicinity of the resort of Belokurikha (Altai Krai) are presented. Functional zoning of the territory of the projected natural park with the allocation of zones of special protection, regulated recreational use and traditional nature management, as well as the buffer (buffer) zone is proposed.